2013
DOI: 10.1063/1.4804283
|View full text |Cite
|
Sign up to set email alerts
|

Note: Mobile micro-Raman analyzer integrated with a lab-on-a-chip

Abstract: A mobile micro-Raman microfluidic analyzer was designed and built for label-free, nondestructive, fingerprint detection of samples on microfluidic chip systems. It mainly includes an optical module (including the Raman detection system and the microscopic imaging system), 3-axis stages with step motors and other auxiliary circuits. The setup of the analyzer was designed with fully considering the characters of the microfluidics system. The experimental results prove that this microfluidics analyzer is practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Scheme 1(b) shows the detailed conguration of the detection zone of the microuidic chip. Subsequently, the nished microuidic chip was installed on a self-built Raman microspectrometer (Supra-1 model) 17 for SERS detection (Scheme 1(c)). Scheme 1(d) and (e) show the results of structure characterizations of Ag nanodots with good uniformity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheme 1(b) shows the detailed conguration of the detection zone of the microuidic chip. Subsequently, the nished microuidic chip was installed on a self-built Raman microspectrometer (Supra-1 model) 17 for SERS detection (Scheme 1(c)). Scheme 1(d) and (e) show the results of structure characterizations of Ag nanodots with good uniformity.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has reported a micro-Raman analyser that copes with this problem in our previous publication. 17 The reported Raman micro-analyser integrates an inverted microscopic imaging system and a Raman detection system for Raman experiments, with a 3-axis stage controlled by step motors for easy positioning of the laser spot onto the detection zone. Furthermore, the optimized setup of the micro-Raman analyser was designed under the consideration of microuidic chips that are oen capped with moulded channels, so the inverted micro-imaging system and the Raman system were under the microuidic chips, minimizing the interference brought about by the cumbersome PDMS cover and circulation tubes, while in the meantime retaining SERS enhancement ability of the substrate during detection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman micro‐spectroscopy has been used for the identification of microorganism . It is now being considered a suitable detection probe with lab‐on‐chip to produce an efficient clinical diagnostic tool . Recently, it has been reported for the prediction of dengue virus infection and plasmodium viral infection in human sera/plasma .…”
Section: Introductionmentioning
confidence: 99%
“…Various methods for the preparation of SERS substrates have been reported, such as atomic layer deposition (ALD) [8], chemical reduction [9], lithography and ion-beamsputtered technique. There are a variety of forms of SERS substrates, such as hydrothermal Au/Ag nano colloids [10], Au/Ag nanoparticles assembled films [11][12][13][14], semi-conductor substrates [15,16] and anodized aluminum oxide templates [17], and so on. One-dimensional nanoscale metal-semiconductor composite materials exhibit distinctive optical, electronic and chemical properties and other interesting applications in catalysis, biomedicine and photonics.…”
Section: Introductionmentioning
confidence: 99%